Germline SMARCE1 mutations predispose to both spinal and cranial clear cell meningiomas. Issue 4 (6th October 2014) - Smith, Miriam J; Wallace, Andrew J; Bennett, Chris; Hasselblatt, Martin; Elert‐Dobkowska, Ewelina; Evans, Linton T; Hickey, William F; van Hoff, Jack; Bauer, David; Lee, Amy; Hevner, Robert F; Beetz, Christian; et al.
Abstract We recently reported SMARCE1 mutations as a cause of spinal clear cell meningiomas. Here, we have identified five further cases with non‐NF2 spinal meningiomas and six with non‐NF2 cranial meningiomas. Three of the spinal cases and three of the cranial cases were clear cell tumours. We screened them for SMARCE1 mutations and investigated copy number changes in all point mutation‐negative samples. We identified two novel mutations in individuals with spinal clear cell meningiomas and three mutations in individuals with cranial clear cell meningiomas. Copy number analysis identified a large deletion of the 5′ end of SMARCE1 in two unrelated probands with spinal clear cell meningiomas. Testing of affected and unaffected relatives of one of these individuals identified the same deletion in two affected female siblings and their unaffected father, providing further evidence of incomplete penetrance of meningioma disease in males. In addition, we found loss of SMARCE1 protein in three of 10 paraffin‐embedded cranial clear cell meningiomas. Together, these results demonstrate that loss of SMARCE1 is relevant to cranial as well as spinal meningiomas. Our study broadens the spectrum of mutations in the SMARCE1 gene and expands the phenotype to include cranial clear cell meningiomas. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd